Effectiveness and Safety of Multicomponent Physical Training in Patients With Chronic Obstructive Pulmonary Disease: Protocol for a Randomized Clinical Trial - Camila Monteiro Mazzarin; Bruna Roberta Silveira; Ana Cristina Lamezon; Bruna Cavon Luna; Silvia Valderramas (SAGE Publishing, 2023)
Background: Currently, most Pulmonary Rehabilitation (PR) programs work with conventional physical training, using resources that are not available in public health in Brazil. Multicomponent physical training is a strategy that uses few resources and can reach a larger portion of the population. Objective: To investigate the effectiveness and safety of multicomponent physical training on physical-functional performance in patients with COPD. Design: Protocol for a randomized clinical trial with 2 groups in parallel (1:1). Setting: University-based, outpatient, physiotherapy clinic. Participants: 64 patients aged ⩾50 years, clinical-functional diagnosis of COPD, GOLD II and III criteria will participate in the study. Intervention: Participants will be randomly allocated into 2 groups: Multicomponent Physical Training-MPT (n = 32): aerobic, strength, balance and flexibility exercises performed in a circuit training format, or Conventional Physical Training-CPT (n = 32): aerobic and strength training. The interventions will be carried out twice a week, for 8 weeks and supervised by the same physiotherapist. Measurements: The 3 primary outcomes are the 6-Minute Walk Test (6MWT), the 6-Minute Step Test (6MST) and VO 2 consumption as measured during the 6MWT. Secondary outcomes will be exercise capacity, level of physical activity in daily life, peripheral muscle strength, functional status, dyspnea, fatigue and quality of life. Safety will be assessed by recording adverse effects. These outcomes will be evaluated before and after the intervention and the evaluator will be blind. Limitations: It will not be possible to perform the blinding of the physiotherapist who will supervise the interventions. Conclusions: This study is expected to demonstrate that MPT using simple resources is an effective and safe intervention for the improvement of the aforementioned outcomes and, in addition, to broaden the horizon of research in relation to new methods of physical rehabilitation for patients with COPD.